The Role of Hypothesis Testing in the Molding of Econometric Models - Kevin D. Hoover (Duke University, Center for the History of Political Economy (CHOPE), 2012)
The paper is a keynote lecture from the Tilburg-Madrid Conference on Hypothesis Tests: Foundations and Applications at the Universidad Nacional de Educación a Distancia (UNED) Madrid, Spain, 15-16 December 2011. It addresses the role of tests of statistical hypotheses (specification tests) in selection of a statistically admissible model in which to evaluate economic hypotheses. The issue is formulated in the context of recent philosophical accounts on the nature of models and related to some results in the literature on specification search.
Keywords: B41; C18; C12; C50; 330; statistical testing; hypothesis tests; models; general-to-specific specification search; optional stopping; severe tests; costs of search; costs of inference; extreme-bounds analysis; LSE econometric methodology